Mechanism of homocysteine-mediated endothelial injury and its consequences for atherosclerosis - Yuan, Deqiang; Chu, Jiapeng; Lin, Hao; Zhu, Guoqi; Qian, Jun; Yu, Yunan; Yao, Tongqing; Ping, Fan; Chen, Fei; Liu, Xuebo (Frontiers in Cardiovascular Medicine, 2023)
Homocysteine (Hcy) is an intermediate amino acid formed during the conversion from methionine to cysteine. When the fasting plasma Hcy level is higher than 15 μmol/L, it is considered as hyperhomocysteinemia (HHcy). The vascular endothelium is an important barrier to vascular homeostasis, and its impairment is the initiation of atherosclerosis (AS). HHcy is an important risk factor for AS, which can promote the development of AS and the occurrence of cardiovascular events, and Hcy damage to the endothelium is considered to play a very important role. However, the mechanism by which Hcy damages the endothelium is still not fully understood. This review summarizes the mechanism of Hcy-induced endothelial injury and the treatment methods to alleviate the Hcy induced endothelial dysfunction, in order to provide new thoughts for the diagnosis and treatment of Hcy-induced endothelial injury and subsequent AS-related diseases.